Pengambilan Keputusan Untuk Berwirausaha Dengan Pengaruh Faktor E-commerce, Sistem Informasi Akuntansi, dan Self Efficacy - Wildani, Fathoni Adi (Jurnal Akuntansi UMMI, 2022)
This study aimed to obtain evidence about the influence of e-commerce on the decision to entrepreneurship, the effect of the use of accounting information systems in decision making for entrepreneurship and the influence of self efficacy on the decision to entrepreneurship. This research was conducted in the Faculty of Economics and Business, University of Muhammadiyah Gresik. Data collection methods used in this research is survey method with questionnaire technique. The population in this study were students majoring in accounting forces in 2017 and 2018 Faculty of Economics and Business University of Muhammadiyah Gresik have status as an active student. The data used in this study are primary data obtained directly by distributing questionnaires to respondents using purposive sampling technique. The data analysis used is multiple linear regression analysis. The results show that e-commerce has positive influence on the decision to entrepreneurship, accounting information systems use a positive influence on the decision to entrepreneurship and self efficacy has positive influence on the decision to entrepreneurship.